Inherited genetic predispositions in F13A1 and F13B genes predict abdominal adhesion formation: identification of gender prognostic indicators. Issue 1 (December 2018) - Gemmati, Donato; Occhionorelli, Savino; Tisato, Veronica; Vigliano, Marco; Longo, Giovanna; Gonelli, Arianna; Sibilla, Maria; Serino, Maria; Zamboni, Paolo
Abstract Abdominal adhesions (AA) account for the most common complication of peritoneal surgery with bowel obstruction being the severest problem in the absence of effective predicting biomarkers. Anti-AA-barriers or adhesiolysis did not completely prevent bowel obstruction, although there is evidence they might reduce related complications requiring reoperation. In addition, gender-related predispositions have not been adequately investigated. We explored the role of coagulation Factor XIII (F13A1 andF13B subunit-genes) in patients following laparotomy, mostly median/lower median incision line. Globally, 426 patients (54%, ♀), were PCR-SNP-genotyped for FXIIIA V34L (rs5985), FXIIIA P564L (rs5982), FXIIIA Y204F (rs3024477) and FXIIIB H95R (rs6003). Patients' clinical phenotypes were: Group-A (n = 212), those who developed AA, and 55.2% of them developed bowel obstruction (subgroup-A1), the remaining were subgroup-A2; Group B (n = 214) were those who did not develop AA (subgroup-B1; 53.3%) or symptoms/complications (subgroup-B2). Among different laparotomy, colon surgery associated with AA at a major extent (OR = 5.1; 3.24–7.8; P < 0.0001) with different gender scores (♀OR = 5.33; 2.32–12.23; P < 0.0001 and ♂OR = 3.44; 1.58–7.49; P < 0.0001). Among SNPs, P564L (OR = 4.42; 1.45–13.4; P = 0.008) and Y204F (OR = 7.78; 1.62–37.3; P = 0.01) significantly predicted bowel obstruction and survival-analyses yielded interesting gender distinctions (♀HR = 5.28; 2.36–11.8; P = 0.00005; ♂HR = 2.22; 1.31–3.85; P = 0.0034). Active compounds preventing AA belong to the anticoagulant/fibrinolysis areas, suggesting them candidate investigation targets. We identified novel prognostic markers to predict AA/bowel obstruction giving insights to design novel therapeutic and gender prevention programs.